Adaptive Support Ventilation as a Sole Mode of Mechanical Ventilation-An Observational Study - Rajbanshi, L.K.; Dali, M.; Karki, S.B.; Khanal, K.; Aryal, B.; Chapagain, K. (Birat Journal of Health Sciences, 2017)
Introduction Adaptive support ventilation (ASV) is a close loop dual control mechanical ventilation mode. This mode can automatically change its parameters to weaning mode once the patient is actively breathing converting volume targeted pressure control mode to volume targeted pressure support mode. We aimed to observe the outcome of the patients ventilated with ASV as a sole mode in terms of duration of mechanical ventilation, duration of weaning from the ventilatory support and length of Intensive care unit (ICU) stay. Methodology We conducted a prospective observational study for the duration of six months (Sept 2015 to Feb 2016) to assess the clinical outcome of the patients ventilated by ASV as a sole mode of ventilation. The study conducted observation of 78 patients without chronic respiratory, renal, hepatic and neurological disease who were admitted in our intensive care unit for invasive ventilatory support. Results Out of the 187 patients who required invasive and noninvasive ventilation, only 78 patients fulfilled the criteria to be included in the study. It was observed that the mean duration of mechanical ventilation was 5.4 days while weaning as well as tracheal extubation was successful within 13 hours of initiation of weaning. The mean duration of ICU stay was found to be 6.3 days. Conclusion We concluded that the patient ventilated by ASV mode were effectively weaned without the need of changing the ventilator mode. However, the safety of ASV mode needs to be established by large randomized control trail in a wide spectrum of patients. Birat Journal of Health Sciences 2016 1(1): 8-12